2016
DOI: 10.1002/ca.22804
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging on the anatomic position of the thyroid gland

Abstract: Thyroid disease is common among elderly patients, frequently necessitating thyroid gland examination, imaging, and surgery. However, no prior studies have determined the effect of age on the anatomic position of the thyroid gland in the anterior neck. We hypothesized that the thyroid gland resides at a more caudal position in the neck in elderly patients as compared to younger patients. Head and neck CT scans were collected from 122 atraumatic patients without thyroid disease aged 18-39 years, 40-59 years, 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…They also reported that the distance between the thyroid gland and the sternal notch decreased with age ( P < 0.001). However, Bann et al () found no difference between age groups in thyroid position relative to the hyoid or cricoid cartilage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They also reported that the distance between the thyroid gland and the sternal notch decreased with age ( P < 0.001). However, Bann et al () found no difference between age groups in thyroid position relative to the hyoid or cricoid cartilage.…”
Section: Discussionmentioning
confidence: 97%
“…However, among individuals with a thyroid mass, there was a significant gender difference in the inferior diameter of the thyroid gland [males 2.16 (±1.16) and females 3.37 (±1.30), P = 0.01, paired sample t ‐test]. Bann et al () observed that the position of the thyroid gland depends on changes in cervical spine height, hyoid to hard palate distance and tracheal angle ( P = 1.7 x 10 −11; r 2 =0.37). They also reported that the distance between the thyroid gland and the sternal notch decreased with age ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…16 However, the type of TGo resection remains controversial. 15 Bann et al, 17 after investigating the effect of age on the distance of the TG from the sternal notch, observed that the TG was 15 mm closer to the sternal notch in patients aged 80 years and over than in patients age group-18-39 years. Thus, surgeons should direct their incision at a mean distance of 20 mm cephalad to the sternal notch.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…Moreover, the gland is likely to reside at a more caudal position in the neck in the elderly as compared to younger individuals, which means that clinicians need to take special account of this fact when surgery is planned (77,78).…”
Section: Hyperthyroidism In the Elderlymentioning
confidence: 99%